Part A: Review on the adaptations of wheat and barley associated with waterlogging resistance/ Part B: Investigating the connection between ethylene and adventitious root growth under waterlogged condition, induced by dissolved starch solution - Cardoso, Victor (2021)
Part A: The effect waterlogged soil can have on plant production is a serious concern for UK wheat and barley farmers. Inhibition of aerobic respiration due to the hypoxic condition of waterlogged soil causes detrimental effects to field crops leading to a loss in yields. Plants can respond to this abiotic stress through regulation of their morphological structure, energy metabolism or via hormonal and signalling adaptations. This review aims to outline the adaptations wheat and barley undertake in morphological structure, respiration, reactive oxygen species damage and plant hormone biosynthesis when subjected to waterlogging stress. Finally, we indicate the areas in which waterlogging research still needs further investigation to better understand waterlogging tolerance in these plant species.